Dietary habits of Samoan adults in an urban Australian setting: a cross-sectional study. Issue 5 (25th August 2015) - Perkins, Kym C; Ware, Robert; Felise Tautalasoo, Lemalu; Stanley, Ranandy; Scanlan-Savelio, Lote; Schubert, Lisa
Abstract: Objective: To describe key characteristics of the dietary habits of Samoans residing in Logan, Queensland and to compare these characteristics with comparable populations. Design: Dietary intake was measured using a self-administered structured questionnaire between December 2012 and March 2013. Demographic characteristics included age and sex. Questionnaire results were compared with data from samples of Brisbane residents of similar social and economic characteristics and Pacific Islanders in New Zealand. The association between demographic characteristics and diet was investigated. Setting: Logan, Queensland, Australia. Subjects: Samoans aged 16 years and older. Results: A total of 207 Samoans participated, ninety-six (46 %) of whom were male. Of the participants, seventy-nine (38 %) were aged 16–29 years, sixty-three (30 %) were aged 30–49 years and sixty-five (31 %) were aged ≥50 years. Younger adults were significantly more likely to eat hamburgers, pizza, cakes, savoury pastries, potato crisps, sweets and soft drinks (all variables P <0·001). Among Samoans, 44·7 % consumed two or more pieces of fruit daily, compared with 43·8 % of comparable Brisbane residents (relative risk=1·0; 95 % CI 0·8, 1·2). Three or more servings of vegetables each day were consumed by 9·2 % of Samoans compared with 36·6 % of comparable Brisbane residents (relative risk=3·8; 95 % CI 2·5, 6·0). Conclusions: Samoans are consuming significantly fewer vegetables and more discretionary foods than other populations. Socio-economic factors, length of stay in Australia and cultural practices may impact upon Samoans' diets. Further comprehensive studies on Samoans' dietary habits in Australia are recommended.